Phase evolution of highly immiscible alloys under shear deformation: Kinetic pathways, steady states, and the lever-rule. (15th October 2017) - Ashkenazy, Yinon; Pant, Nirab; Zhou, Jian; Bellon, Pascal; Averback, Robert S.
Abstract: Phase evolution of dilute, highly immiscible, Cu alloys (Cu-Nb, Cu-V, and Cu-Ta) during low-temperature severe plastic deformation was investigated using large-scale molecular dynamics simulations. At low solute concentrations, each system maintained a FCC structure in steady state, but as the concentration was increased above a saturation limit (0.3 at.% for Ta, 1 at.% for Nb and 5 at.% for V), the system became two-phase, comprising co-existing FCC and amorphous phases. Unlike Cu-Nb and Cu-V, the amorphous phase in the Cu-Ta system showed strong solute partitioning. Increasing the solute concentration above a second phase boundary (8 at.% V, 9 at.% Nb, and 24 at.% Ta) led to complete amorphization. Throughout the two-phase region, the compositions of the FCC and amorphous phases remained nearly constant, thus following the lever rule. Initiating the systems either as a FCC homogeneous alloy, or with a BCC sphere embedded in a Cu matrix, had no effect on the steady state microstructure, implying uniqueness of the steady state under low-temperature shear deformation. Lastly, chemical order and phase partitioning in the amorphous Cu-Ta system under low-temperature shear is found remarkably similar to that in the equilibrium structure above the melting temperature. Graphical abstract: Image 1